Interactions of Cu substrates with titanium-alloyed Sn-Zn solders - Soares, Delfim (2006)
The interactions of copper substrate with titanium-alloyed Sn-Zn eutectic solders have been studied. Two series of experiments have been performed. The first one consisted in differential thermal analyses of Sn-Zn nearly eutectic alloys containing from 1.3 to 2.2 wt. % Ti. Diffusion couples consisted of Cu-wires and Sn-Zn-Ti liquid solders, produced at 250 and 275 OC have been prepared in the second series,. The contact times were up to 3600 s. The contact zones have been characterized by optical and scanning electron microscope. Two layers have been found along the interfaces solid/liquid. The first and the second layers are identical, respectively, with γ and ε phases of the Cu-Zn system. No changes of the chemical compositions were detected for the tested temperatures and reaction times. Continuous parabolic growth of the total diffusion zone thickness with the time of diffusion is observed. The growth is due mainly to one the formed layers (γ ) while the thickness of the ε-phase layer, stays almost constant for all tested diffusion times and temperatures.